Solve one equation for x (or y), then substitute that value into the other equation.
Example: x-2y=5, so x=2y+5
Now substitute this for x in "5x-2y=5"
5(2y+5) - 2y = 5
10y + 25 - 2y = 5
8y = -20
y = -20/8 = -5/2
Put this value for y back into your first equation to solve for x:
x = 2y + 5
x = 2(-5/2) + 5
x = -5+5
x = 0
ANSWER: x=0, y=-5/2
2006-11-05 05:58:16
·
answer #1
·
answered by Anonymous
·
2⤊
0⤋
5x - 2y = 5 - - - - - -Equation 1
x - 2y = 5 - - - - - - -Equation 2
- - - - - - - - - - -
Substitute method Equation 2
x - 2y = 5
x - 2y + 2y = 5 + 2y
x = 5 + 2y
Insert the x value into equation 1
- - - - - - - - - - - - - -
Solving for y
5x - 2y = 5
5(5 + 2y) - 2y = 5
25 + 10y - 2y = 5
25 + 8y = 5
25 + 8y - 25 = 5 - 25
8y = - 20
8y/8 = - 20/8
y = - 2 4/8
y = - 2 1/2
y = - 2.5
The answer is y = - 2.5
Insert the y value into equation 2
- - - - - - - - - - - - - - - - - - -
Solving for x
x - 2y = 5
x - 2(- 2.5) = 5
x - ( - 5) = 5
x+5 = 5
x+5 -5 = 5 -5
x = 0
The answer is x = 0
Insert the y value into equation 2
- - - - - - - - - - - - - - - - - - -
Check for equation 2
x - 2y = 5
0 - 2(- 2.5) = 5
0 +5= 5
5 = 5
- - - - - - - - - - - - - - - - - - - -
Check for equation 1
5x - 2y = 5
5(0) - 2(- 2.5) = 5
0 - (- 5) = 5
0 + 5 = 5
5 = 5
- - - - - - - - - - - - - - - - - -
The solution set is { 0, - 2.5 }
- - - - - - - - - - - - - - - - - - - - s-
2006-11-05 06:43:18
·
answer #2
·
answered by SAMUEL D 7
·
0⤊
0⤋
If x is the same in both equations and y is the same in both equations then you solve by setting 5x-2y=x-2y (because both sides of the equation equal 5). If you add 2y to both sides of the equation (5x-2y+2y=x-2y+2y) then you eliminate the 'y' variable, and 5x=x. There is only one answer to the value of x. I'll let you figure that out.
2006-11-05 06:05:07
·
answer #3
·
answered by David A 5
·
1⤊
0⤋
Using the second equation and simple algebra, you can get x = 2y + 5. Then, take that expression for x and substitute it into the first equation to get an equation in y only, which you can solve with more algebra. Once you have a value for y, substitute it into either equation (the second would be easier) to solve for x, which would then be the only variable in the equation.
2006-11-05 06:01:25
·
answer #4
·
answered by DavidK93 7
·
1⤊
0⤋
On the x-2y=5 equation, subtract x on both sides:
-2y=-x+5
Divide -2 on both sides:
y=1/2x-5/2
Take the equation and plug into the 5x-2y=5 equation:
5x-2(1/2x-5/2)=5
5x-x+5=5
4x+5=5
4x=0
x=0
Take 0 and plug it in x:
5(0)-2y=5
-2y=5
y=-5/2
(0,-5/2)
Check:
5(0)-2(-5/2)=5
-2(-5/2)=5
5=5
0-2(-5/2)=5
-2(-5/2)=5
5=5
I hope that was helpful!
2006-11-05 06:25:15
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
well let me help you
5x-2y=5
x-2y=5 / (-1)
and you obtain
5x-2y=5
-x+2y=-5 now you add the 1st ecution to the 2nd like this
5x+(-x)-2y+2y=5-5
next step
4x=0
x=0
now we know that x=0 and we "introduce" x into the 1st equation
5*0-2y=5
-2y=5
y=-5/2
if you would like to use the substitution method i can show it to you.
2006-11-05 06:10:47
·
answer #6
·
answered by Pavel 1
·
1⤊
0⤋
x-2y=5
x=5+2y
sub in the other equation
5(5+2y)-2y=5
25+10y-2y=5
8y=-20
y=-2.5
x=5+2(-2.5)=0
so x=0 and y=-2.5 or -5/2
2006-11-05 06:01:56
·
answer #7
·
answered by raj 7
·
2⤊
0⤋
5x-2y=5 ,x-2y=5
5x=2y+5 ,x=2y+5
5(2y+5)= 2y+5
10y+25=2y+5
8y+25=5
8y=(-20)
y= (-5)/2 or (-2.5)
x=2(-2.5)+5
x=-5+5
x=0
2006-11-05 06:03:58
·
answer #8
·
answered by Anonymous
·
1⤊
0⤋
Solve one of the equations for x or y, then substitute that into the other
2006-11-05 06:04:08
·
answer #9
·
answered by futureastronaut1 3
·
1⤊
0⤋